A Molecular and Whole Body Insight of the Mechanisms Surrounding Glucose Disposal and Insulin Resistance with Hypoxic Treatment in Skeletal Muscle - R. W. A. Mackenzie; P. Watt (Journal of Diabetes Research)
Although the mechanisms are largely unidentified, the chronic or intermittent hypoxic patterns occurring with respiratory diseases, such as chronic pulmonary disease or obstructive sleep apnea (OSA) and obesity, are commonly associated with glucose intolerance. Indeed, hypoxia has been widely implicated in the development of insulin resistance either via the direct action on insulin receptor substrate (IRS) and protein kinase B (PKB/Akt) or indirectly through adipose tissue expansion and systemic inflammation. Yet hypoxia is also known to encourage glucose transport using insulin-dependent mechanisms, largely reliant on the metabolic master switch, 5′ AMP-activated protein kinase (AMPK). In addition, hypoxic exposure has been shown to improve glucose control in type 2 diabetics. The literature surrounding hypoxia-induced changes to glycemic control appears to be confusing and conflicting. How is it that the same stress can seemingly cause insulin resistance while increasing glucose uptake? There is little doubt that acute hypoxia increases glucose metabolism in skeletal muscle and does so using the same pathway as muscle contraction. The purpose of this review paper is to provide an insight into the mechanisms underpinning the observed effects and to open up discussions around the conflicting data surrounding hypoxia and glucose control.